Young children’s parents’ interest in and around Győr in neuropedagogy (Training and Practice : Journal of Educational Sciences, 2020)
Neuropedagogy may be one, if perhaps not the most important stage in the current history of pedagogy, as this children-centred science seeks to shape pedagogical practice based on the latest brain research findings, helping both educators and students. In my online empirical research with 315 participants, I aimed to reveal the prior knowledge and attitudes of parents with small children towards this unfolding paradigm. Most of them positively expressed their interest, showing a need for further and more extensive knowledge. A significant part of the research participants would enrol their child in an institution or class with the aforementioned orientation. Based on my findings openness is clearly visible, therefore, it would be worthwhile to translate scientific knowledge into the “parents’ language” so that neuropedagogy could beaccessed, easily interpreted and integrated into the everyday lives of those involved in education.